2015
DOI: 10.1016/j.adengl.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Necrobiosis Lipoidica: A Descriptive Study of 35 Cases

Abstract: NL is frequently associated with type 1 and 2 diabetes. Although diabetes tends to develop before NL, it can occur simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…Necrobiosis lipoidica is a chronic granulomatous dermatitis, and the peak age for presentation has been reported to be in the third and fourth decades . It is very rare in the pediatric population, and only a few isolated cases have been reported in individuals below the age of 10 years, all of which were patients with diabetes .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Necrobiosis lipoidica is a chronic granulomatous dermatitis, and the peak age for presentation has been reported to be in the third and fourth decades . It is very rare in the pediatric population, and only a few isolated cases have been reported in individuals below the age of 10 years, all of which were patients with diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…Lesions on the face, scalp, trunk, groin, and upper extremities have also been reported . In a study of 35 patients by Marcoval et al, the authors found only 1 patient who had lesions in areas other than tibial region . There are few case reports of NL affecting the back, and none were in children .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudios posteriores han disminuido esta cifra hasta situarla en el 11%, si bien, en el seguimiento posterior a cinco años, hasta un 5 % más de los pacientes estudiados desarrollaron DM o intolerancia a la glucosa 5 . En un reciente estudio publicado por un grupo español donde se incluyen 35 pacientes con NL, se calcula una prevalencia de DM del 65 % 6 .…”
Section: Etiopatogenia Y Asociación a Otros Procesosunclassified